Implications of technological advancement of surgery in low and middle-income countries’ a narrative review - Samreen Malik; Samir Azeem; Amna Rehman; Hijab Khan; Arifa Haque; Afshan Qamar (Journal of the Pakistan Medical Association, 2024)
Countries that are striving to keep pace with emerging technologies in surgical practices and still not able to cope with exemplary international standards are in dire need of resources to build and strengthen their healthcare system. This review focusses on the impeding factors that hinder in adaptation of advanced technology and machinery in the health care industry. Considering the immense potential for current surgical technologies to transform the delivery of healthcare, their implementation in LMICs confronts considerable challenges due to lack of infrastructure, human capital and inadequate resources. To address these difficulties, various entities, including healthcare institutions, government and non-governmental organisations, and foreign partners, must work together. Building capacity through intended education and training initiatives, building infrastructure, and collaborative partnerships are critical for overcoming hurdles to effective deployment of surgical technology in low-income communities of the world. Keywords: Capacity Building, Health Care, Technology, Digital surgery, LMICs, innovation.